2013
DOI: 10.1111/pcmr.12078
|View full text |Cite
|
Sign up to set email alerts
|

Photoaging of human retinal pigment epithelium is accompanied by oxidative modifications of its eumelanin

Abstract: Although photodegradation of the retinal pigment epithelium (RPE) melanin may contribute to the etiology of age-related macular degeneration, the molecular mechanisms of this phenomenon and the structural changes of the modified melanin remain unknown. Recently, we found that the ratio of pyrrole-2,3,4,5-tetracarboxylic acid (PTeCA) to pyrrole-2,3,5-tricarboxylic acid (PTCA) is a marker for the heat-induced cross-linking of eumelanin. In this study, we examined UVA-induced changes in synthetic eumelanins to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 60 publications
(110 reference statements)
5
71
1
Order By: Relevance
“…To identify the presence of melanin in the fossil material, the alkaline hydrogen peroxide oxidation method [24][25][26][27] was used in the black to dark brown-coloured fossil eye fragments and the light brown-coloured rock matrix. Samples (8-17 mg) were ground to a fine powder using a mortar and pestle and added to water at a concentration of 10 mg per ml water and 100 ml aliquots were subjected to alkaline hydrogen peroxide oxidation 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify the presence of melanin in the fossil material, the alkaline hydrogen peroxide oxidation method [24][25][26][27] was used in the black to dark brown-coloured fossil eye fragments and the light brown-coloured rock matrix. Samples (8-17 mg) were ground to a fine powder using a mortar and pestle and added to water at a concentration of 10 mg per ml water and 100 ml aliquots were subjected to alkaline hydrogen peroxide oxidation 25 .…”
Section: Discussionmentioning
confidence: 99%
“…These molecules are common only to eumelanin and have never been produced by the alkaline hydrogen peroxide oxidation of any other biological material [24][25][26] . The PTeCA/PTCA ratio of 2.7 is extremely high as compared with those of extant fish retina (0.10 in Table 1) and bovine retinal pigment epithelium melanosomes (0.13), indicating extensive thermal modification of eumelanine 26,27 . The retinal area of A. bridgei has many mineralized rods, each about 2 mm wide and maximum length of about 18 mm (Fig.…”
Section: Morphology Of Granules Fossils Of the Acanthodian Fishmentioning
confidence: 99%
“…There is also a loss of melanin and the remaining melanin granules exhibit substantially modified physicochemical properties that may reduce the antioxidant and photoprotective ability of RPE melanin and even enhance its phototoxic potential [3][4][5][6]. It has recently been demonstrated that RPE melanin from aged human donors exhibits substantial oxidative modifications and crosslinking, which might be aggravated by chronic exposure to shortwavelength visible light (402-508 nm) [7]. To study in vitro these age-related changes that in vivo occur over many years, we proposed a simple model of photoaging of RPE melanin, in which bovine or porcine RPE melanosomes were exposed to intense visible light to induce different degree of their photobleaching [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…15 Melanosomes may be lost by extrusion through the basal membrane of the epithelium into Bruch’s membrane, where they might be dissolved by macrophages. Melanosomes are also subject to photo-toxicity 16 which can be modulated by lipofuscin. 17 …”
Section: Discussionmentioning
confidence: 99%